Transparency Duties in Italian Universities - Daniele Valerio (Symphonya, 2017)
The Legislative Decree no. 33/2013 and subsequent amendments and additions involved large areas of the public sector, including state universities, which are subject to the publication obligations affecting most Italian administrations. The absence of specific guidelines on the subject, also due to the co-presence of different authorities, leaves operators to the difficult reconciliation between the specificity of the university system and the generality of regulatory obligations.